BANKRUPTCY ANALYSIS USING THE GROVER AND ZMIJEWSKI METHOD AT PT ENVY TECHNOLOGIES INDONESIA TBK FOR THE PERIOD 2022-2024 - Sudirman; Yahya, Muh; Lutfi, Anugrah (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
Bankruptcy in technology companies, both startups and public companies, is a common problem due to liquidity pressures, capital structure imbalances, failed business strategies, and external factors such as global economic turmoil and regulatory changes. This study aims to analyze the bankruptcy potential of PT Envy Technologies Indonesia Tbk using the Grover (G-Score) and Zmijewski (X-Score) models. Data are taken from the company's financial statements for the 2022–2024 period obtained through the Indonesia Stock Exchange. The analysis shows that the company is in an unhealthy financial condition, with low profitability, high debt, and weak liquidity. Although ROA improved in 2024, this condition was not enough to offset the significant financial burden. Governance issues such as alleged corruption, late financial reporting, and OJK sanctions exacerbate the situation. This study recommends comprehensive restructuring, operational efficiency, debt renegotiation, increased liquidity, a focus on core business lines, and management transparency to avoid bankruptcy or liquidation.